Percepção auditiva de crianças com transtorno do espectro autista : criação de um instrumento de avaliação - Melo, Adriana Benevides Duarte Leite (2023)
Introduction: Autism Spectrum Disorder involves genetic, neurological and social factors in children and adolescents, being considered a developmental disorder, classified at different levels of severity. Hyperacusis and changes in auditory perception are observed in individuals with this disorder. Assessment can be carried out through questionnaires and behavioral and electrophysiological auditory exams. Objective: To develop an instrument to assess auditory perception and hyperacusis in children with autism spectrum disorder. Method: This dissertation is divided into two studies: 1) Integrative review with electronic search in the Pubmed/Medline, Scopus, Scielo and LILACS databases to analyze the existing scientific literature on hyperacusis and auditory perception in people with autism spectrum disorder, in addition to the protocols used to identify these changes in this audience. Peer-reviewed articles published between 2013 and 2023 were included. Article selection and data extraction were carried out by two blind and independent reviewers. Disagreements were resolved by consensus. Data analysis was performed descriptively. 2) The second was to create a questionnaire containing items covering consciousness functions, orientation functions and auditory questions and obtain its validation by applying it to 11 specialist judges in speech therapy, with clinical practice in the area for more than 5 years. The collection was carried out using Google Forms. Results: 1) Regarding the integrative review, the publications addressed auditory assessment and electrophysiological assessment with the purpose of verifying the presence of hearing loss, hyperacusis, but the studies did not present specific protocols for evaluating auditory perception in people with ASD, except the Questionnaire of ABQ auditory behavior, which was not found in the validated Portuguese version. 2) The instrument was structured into 10 items, containing aspects about consciousness functions, orientation functions and auditory issues. The first stage of validation was the evaluation of the domains: behavioral, objectivity, simplicity, clarity, relevance, precision and variety, which were evaluated by 11 speech therapists’ experts in the area of ASD, according to Content Validity (CVI) calculations, Ratio of Content Validity (CVR) and Kappa coefficient. The judges' level of agreement was 100% in domains 1 and 2 (orientation functions, auditory perception) and 80% in domain 3 (auditory functions), indicating that they are adequate. Conclusion: 1) The review suggests the importance of developing risk instruments for hyperacusis that assess auditory perception in people with ASD. 2) The instrument can evaluate auditory sensitivity, analyzing auditory perception in children with ASD, directing parents and/or guardians and assisting the clinical practice of speech therapists for an early diagnosis.